Real life experience on the use of Remdesivir in patients admitted to COVID-19 in two referral Italian hospital: a propensity score matched analysis - Nicola Veronese; Francesco Di Gennaro; Luisa Frallonardo; Stefano Ciriminna; Roberta Papagni; Luca Carruba; Diletta Agnello; Giuseppina De Iaco; Nicolò De Gennaro; Giuseppina Di Franco; Liliana Naro; Gaetano Brindicci; et al. (Scientific Reports, 2024)
Abstract Remdesivir (RDV) was the first Food and Drug Administration (FDA)-approved medication for COVID-19, with discordant data on efficacy in reducing mortality risk and disease progression. In the context of a dynamic and rapidly changing pandemic landscape, the utilization of real-world evidence is of utmost importance. The objective of this study is to evaluate the impact of RDV on patients who have been admitted to two university referral hospitals in Italy due to COVID-19. All patients older than 18 years and hospitalized at two different universities (Bari and Palermo) were enrolled in this study. To minimize the effect of potential confounders, we used propensity score matching with one case (Remdesivir) and one control that never experienced this kind of intervention during hospitalization. Mortality was the primary outcome of our investigation, and it was recorded using death certificates and/or medical records. Severe COVID-19 was defined as admission to the intensive care unit or a qSOFAscore ≥ 2 or CURB65scores ≥ 3. After using propensity score matching, 365 patients taking Remdesivir and 365 controls were included. No significant differences emerged between the two groups in terms of mean age and percentage of females, while patients taking Remdesivir were less frequently active smokers (p < 0.0001). Moreover, the patients taking Remdesivir were less frequently vaccinated against COVID-19. All the other clinical, radiological, and pharmacological parameters were balanced between the two groups. The use of Remdesivir in our cohort was associated with a significantly lower risk of mortality during the follow-up period (HR 0.56; 95% CI 0.37–0.86; p = 0.007). Moreover, RDV was associated with a significantly lower incidence of non-invasive ventilation (OR 0.27; 95% CI 0.20–0.36). Furthermore, in the 365 patients taking Remdesivir, we observed two cases of mild renal failure requiring a reduction in the dosage of Remdesivir and two cases in which the physicians decided to interrupt Remdesivir for bradycardia and for QT elongation. Our study suggests that the use of Remdesivir in hospitalized COVID-19 patients is a safe therapy associated with improved clinical outcomes, including halving of mortality and with a reduction of around 75% of the risk of invasive ventilation. In a constantly changing COVID-19 scenario, ongoing research is necessary to tailor treatment decisions based on the latest scientific evidence and optimize patient outcomes.